Acute Graft-Versus-Host Disease After Humanized Anti-CD19-CAR T Therapy in Relapsed B-ALL Patients After Allogeneic Hematopoietic Stem Cell Transplant - Liu, Pengjiang; Liu, Meijing; Lyu, Cuicui; Lu, Wenyi; Cui, Rui; Wang, Jia; Li, Qing; Mou, Nan; Deng, Qi; Yang, Donglin (Frontiers in Oncology, 2020)
We studied the acute graft-versus-host disease (GVHD) post humanized anti-CD19-CAR T therapy for relapsed B-ALL patients after allogeneic hematopoietic stem cell transplant (allo-HSCT). Fifteen B-ALL patients were enrolled in our study. Thirteen patients (86.67%) achieved complete response (CR) or CR with incomplete count recovery. The donor chimerism of the thirteen patients rised to 99.86+0.21%. Development of aGVHD was observed in ten patients (66.67%). Six patients developed grade I-II of aGVHD, while the other four patients developed grade III-IV of aGVHD. The notable adverse events were grade 1-2 cytokine release syndrome (CRS) in ten patients and grade 3-4 CRS in five patients. Two patients died of infection, while another patient died of sudden cardiac death. The anti-CD19-CAR T cells were not completely eliminated in peripheral blood when the patients developed aGVHD. But we did not observe its expansion peaks again in the process of aGVHD. During the aGVHD, the peaks of the IL-6 and TNF-a were correlated with aGVHD levels. By May 31, 2020, the rates of LFS and OS on 180 days were 53.846% and 61.638%. All the patients who survived to date experienced aGVHD after humanized anti-CD19-CAR T cell therapy.